2015
DOI: 10.1109/tifs.2014.2363951
|View full text |Cite
|
Sign up to set email alerts
|

Learning Fingerprint Reconstruction: From Minutiae to Image

Abstract: Abstract-The set of minutia points is considered to be the most distinctive feature for fingerprint representation and is widely used in fingerprint matching. It was believed that the minutiae set does not contain sufficient information to reconstruct the original fingerprint image from which minutiae were extracted. However, recent studies have shown that it is indeed possible to reconstruct fingerprint images from their minutiae representations. Reconstruction techniques demonstrate the need for securing fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Other studies went even further by constructing a fingerprint image from minutiae. The results showed that there is a very high resemblance between the original and the reconstructed fingerprint [38]. Ben-Asher et al suggested a two-step authentication method where the fingerprint, combined with the touchscreen, is used to verify or identify the user [39].…”
Section: Motion Sensorsmentioning
confidence: 99%
“…Other studies went even further by constructing a fingerprint image from minutiae. The results showed that there is a very high resemblance between the original and the reconstructed fingerprint [38]. Ben-Asher et al suggested a two-step authentication method where the fingerprint, combined with the touchscreen, is used to verify or identify the user [39].…”
Section: Motion Sensorsmentioning
confidence: 99%
“…It, therefore, leaves the scene much cleaner than when using black powder. 63,64 Patent fingerprints can be made by blood, grease, ink or dirt. This type of fingerprint is easily visible to the human eye.…”
Section: Fingerprints Found In Scene Of Crimementioning
confidence: 99%
“…For instance, as smartphones and IoT-enabled devices are always connected to network, the system is easily exposed to diverse attacks [5], which cause permanent loss of private biometric information. According to [6], [7], [8], [9], original fingerprint images could be reconstructed from their ge-ometrical minutia data, so if a hostile entity compromises the fingerprint template, the biometric identity cannot be used permanently [10]. For secure protection of fingerprint templates, a cancelable fingerprint template [11], [12], [13], [14] and bio-encryption [15], [16] have been proposed [17], [18], however, some of these solutions can only be adopted when the fingerprint is represented by an ordered and fixed-length bit-vector [13], [14], [19].…”
Section: Introductionmentioning
confidence: 99%